Laying Down Paths in Talking with a Dutch Canadian Organizational Communication Ethnographer - Boris H. J. M. Brummans; Marie-Claude Plourde (Communiquer)
This interview traces the unfolding trajectories of Boris Brummans, an organizational communication ethnographer, in conversation with Marie-Claude Plourde.